ผลกระทบของความสามารถในการเข้าถึงระบบรถไฟฟ้าขนส่งมวลชนต่อราคาอาคารชุดที่พักอาศัยในเขตกรุงเทพมหานคร - อภิชาต อึ้งประเสริฐ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
While the construction costs of mass rapid transit system are very high, upon completion of the system, prices of real estate properties nearby ten to increase substantially. This presents an opportunity for the government to recoup its investment. However, there has been no systematic study in Thailand that relates the impacts of mass rapid transit system to property prices, which allow the government to estimate potential revenues that may be generated by such captitalization. To shed light on this issue, this thesis has two objectives; 1)to determine the relationship between condominium prices and their distances to transit station which reflect the abillity of residents of access the mass rapid transit system, and 2) to estimate statistical models, that can be used to predict condominium prices. The data used in this study were gathered from real-estate magazines, government agencies websites and digital maps, and were analyzed using Hedonic Regression technique. The estimation results showed that the price of condominium is a function of the square root of distance from transit station. Controlling for property attributes, the further from transit station the property is, the lower the price. Prices decline faster near transit station and more slowly at further location. The estimated rent gradient implies that a property adjacent to transit station is 680,000 Baht more expensive than one that is located two kilometers away from the station, and 970,000 Baht more than one that is located two kilometers away. The results can be used to predict the revenues that can be raised from property tax hike which can in turn be used to finance further expansion of the transit system.